2017
DOI: 10.1002/lary.26836
|View full text |Cite
|
Sign up to set email alerts
|

Urban and rural differences in outcomes of head and neck cancer

Abstract: 2c. Laryngoscope, 128:852-858, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 49 publications
3
28
2
Order By: Relevance
“…This group proposed that Canada's distributed model of care across geographic catchment areas may be effective in minimizing urban-rural disparities. 6 Further comparative studies may elucidate political and economic factors that impact access to care for this population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This group proposed that Canada's distributed model of care across geographic catchment areas may be effective in minimizing urban-rural disparities. 6 Further comparative studies may elucidate political and economic factors that impact access to care for this population.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to prior studies, Kim et al found no difference in overall survival between urban and rural head and neck cancer patients in their cohort in British Columbia. This group proposed that Canada's distributed model of care across geographic catchment areas may be effective in minimizing urban–rural disparities 6 . Further comparative studies may elucidate political and economic factors that impact access to care for this population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Other studies have reported increased incidence, adverse outcomes in urban dwellers, 18 or no rural-urban disparities. 19 Age at diagnosis is an important prognostic factor in all types of cancers, and HNC is no exception. Some studies report better prognosis in young patients, [20][21][22] while others report differently.…”
Section: Introductionmentioning
confidence: 99%